Education in Sassanide State 224-651 A.D - Abdulwahid, Kalthoma; Rasheed , Arsan; عماد عبدالقادر بریفكانی (Humanities Journal of University of Zakho, 2021)
There are many concrete evidences on education in Sassanide times particularly supported from Avesta , Zoarest speeches and clergymen’s instructions .In Sassanian period education is confined mainly to education of princes, the nobility and the clergy. Most peasants were illiterate, but most urban merchants were probably acquainted at least with writing and calculation. The education in Sassanian period can be classified into two stages : A. Education commenced from home : The required education for a child of a noble or an upper-class family would begin attending school at the “proper age,” between five and seven years while children of lower class , their parents were their teachers. B. Education outside home In this stage the apprentice would have completed general training and religious studies by the age of fifteen years . Inside sassanian palace temple ( church ) there was a kind of school where The princes were taught in the palace how to write. Furthermore , they learned the Pahlavi translation of the Avesta .Then after graduation from this educational stage they were taught many arts such as literature , history , rhetorics and training in horsemanship, archery, hunting , music and astronomy were strongly part of educational curriculum . Thus Sassanians gave great importance to both aspects of education : physical education and thought education The purpose of education in Sassanide period had many targets including nation-_building and State -_building to serve their religion , state and people. Keywords: education , Zoarestrian , clergymen , nation-_building